(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2026)
The 2009 earthquake in Padang, Indonesia, caused significant damage to heritage assets, posing challenges to preserving their authenticity during recovery. This study examines the implementation of the Nara Protocol’s six authenticity attributes traditions and techniques, form and design, use and function, materials and substance, spirit and feeling, and location and setting in participatory community-led heritage recovery efforts. The objective is to assess how the recovery process aligns with the Nara Protocol’s principles of contextual authenticity while addressing local cultural values. A mixed-method approach was employed, including field surveys of damaged heritage structures, stakeholder interviews, and document analysis of pre- and post-disaster records. The results indicate various implementations of the six authenticity attributes, leading to alterations in authenticity. Religious and community buildings show more changes in materials and techniques due to the availability of present-day materials and the built-back-better principle, aiming to provide safer buildings and environments for future earthquakes. The lack of sufficient documentation challenges restoration efforts post-disaster, resulting in changes in shape and design. Advocacy from experts, universities, ancestors, and donors supports these conservation efforts. This study also highlights that community involvement is crucial to ensure the authenticity of spirit and feeling post-recovery.